IN VITRO ANTIOXIDANT AND ANTIHYPERGLYCEMIC ACTIVITIES OF HYDROETHANOLIC LEAF EXTRACT OF ACACIA CATECHU (L.F) WILLD - B, Ramesh; V, Jayabharathi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to analyze the antioxidant and antihyperglycemic activities of hydroethanolic leaf extract of Acacia catechu (L.f) Willd. Methods: The A. catechu (L.f) Willd. leaf extract was subjected to antioxidant activities such as 1,1-diphenyl-1-picryl hydrazyl (DPPH), hydroxyl radical (OH−), nitric oxide radical (NO−), and superoxide radical (SO) scavenging assays. Further, the leaf extract was subjected to antihyperglycemic activity by α-amylase inhibition assay. Results: The free radical scavenging activity of the plant extract was found to increase with increase in concentration (20-100 μg/ml) and the maximum activity was obtained at 100 μg/ml, which was compared with the standard ascorbic acid. The percentage inhibition of free radicals was found to be 62.94±0.91%, 63.53±1.08%, 71.04±0.48%, and 51.50±0.86% for DPPH, OH−, NO−, and SO−, respectively. The IC50 for DPPH, OH−, NO−, and SO were recorded as 73.81±0.95, 69.03±0.58, 60.74±0.37, and 83.10±1.00 μg/ml. The IC50 value of α-amylase inhibitory activity was found to be 71.17 μg/ml. Conclusion: The present investigations suggest that the A. catechu (L.f) Willd may serve as a potential source of natural antioxidant and antihyperglycemic agent that could have great importance in pharmaceutical preparations.